The Influence of Sowing Date on Growth, Yield and Qualityof Sugar Cane - M. Towm, Abdalla; A. Moharned, Habiballa; S. Ali, Mirghani (Gezira Journal of Agricultural Science; Vol 1 No 1 (2003), 2021)
This study was conducted within the commercial field of New Halfa Sugar Scheme, during the period October 1994 to September 1996 to determine the influence of sowing date on sugar cane growth, yield and quality. Climatic elements including temperature, percent relative humidity (%RH) and total rainfall were obtained from Halfa meteorological substation. Soil moisture and actual evaportranspiration (ET( during the growth period were measured. Penman evaporation (E (was calculated. Gernnination percentage, plant population,  plant height, stalk thickness, number of intenodes per stalk, fresh and dry mutter content, pithyness, flowering percentage, brix ( %), purity (%), pol  (%), recovery and fiber (%) were determined. The results showed that July and October planting dates were of signi- ficantly higher values for the different aspects of thermal time, crop factors, germination (%( tiller-ing, (%), plant height, dry matter production, final yield and sugar quality as compared to the late sowing date in March. Pithyness was associated with March planting and decreased with July planting Flowering occurred only in the crop planted in March. The water requirements of the crop differed from the existing indenting system where about 18.6 m 3 /feddn(f)/day were required during initial stage, 24.3 m 3 / f/day were required during the development stage, 41.28 /m 3 /f/day were required during the mid season stage and 25.8 m 3 /f/day were required during the late season stage whereas 31,6 m 3 /f/day were required as an average for the whole cycle of cane plant. Sugar cane crop required about 314, 1274, 3092 and 4204 accumulated degree days for initiation, development, mid season and maturity, respectively, for optimal productivity. The late planting date in March exposed the crop to harmful effects of heat stress resulting in poor germination and low yield.